Discovery of the chelonine tribe Adeliini Viereck, 1918 (Hymenoptera: Braconidae) from the Indian subcontinent with the description of a new genus from south India - Ranjith, A.p.; van Achterberg, C.; Samartsev, K.g.; Nasser, M. (Zootaxa, 2021)
The small chelonine tribe Adeliini is one of the derived groups with the postpectal carina absent, which is considered to be an apomorphic character for the Cheloninae. Adeliine genera generally exhibit a narrow endemism although the genus Adelius is widely distributed. Adeliini are reported from the Indian subcontinent for the first time with the description of a new genus and a new species, Carinadelius medicus Ranjith & van Achterberg gen. et sp. nov. from south India. A revised key to the genera of Adeliini is provided with the illustrations of all included genera. The genus Myriola, which was previously included under Adelius, is re-instated based on morphological characters. The New World species of the genus Paradelius are transferred to Sculptomyriola Belokobylskij: Sculptomyriola neotropicalis (Shimbori & Shaw, 2019), S. nigra (Whitfield, 1988) and S. rubra (Whitfield, 1988) are new combinations.